The NPC1L1 Gene Exerts a Notable Impact on the Reduction of Low-Density Lipoprotein Cholesterol in Response to Hyzetimibe: A Factorial-Designed Clinical Trial - Liao, Jianwei; Yang, Liyun; Zhou, Luping; Zhao, Hongbin; Qi, Xiao; Cui, Yimin; Ouyang, Dongsheng (Frontiers in Pharmacology, 2022)
Background: Hyzetimibe is a novel inhibitor of cholesterol that specifically targets the NPC1L1 gene. Significant inter-individual variability suggests the existence of an abundance of poor responders and non-responders. In addition, the current literature is inconsistent and controversial regarding the potential impact of the Niemann-Pick C1-Like 1 (NPC1L1) gene on low-density lipoprotein cholesterol (LDL-C) reduction. In light of these concerns, we performed a high-quality clinical trial to investigate the specific characteristics of NPC1L1 gene variation on LDL-C reduction. Methods: This was a multicenter, randomized, double-blind, placebo-controlled, clinical trial with a factorial design. Qualified patients were randomly assigned to one of six treatments: placebo, hyzetimibe (10 or 20 mg), atorvastatin, and atorvastatin plus hyzetimibe (10 or 20 mg). Fasting blood samples were collected and genotyped, and the concentrations of LDL-C and the targeted drug trough were determined to investigate the association between the NPC1L1 gene expression and the reduction of LDL-C. Results: In total, 727 individuals were initially recruited; of these, 444 were eligible to begin the trial. We identified one SNP (g1679C > G) that exerted significantly different impacts on LDL-C levels. As monotherapy, CC carriers experienced significantly higher reductions in the mean LDL-C (−23.99%) than either the GG (−16.45%, p < 0.01) or GC (−13.02%, p < 0.01) carriers in the hyzetimibe (20 mg) group. In contrast, when co-administered with atorvastatin, GC carriers experienced greater LDL-C reduction than non-GC carriers (-52.23% vs. −45.03%) in the hyzetimibe (20 mg) plus atorvastatin group. Furthermore, the proportions of individuals experiencing a reduction in LDL-C by >50% increased as the dose of hyzetimibe increased from 16.1% to 65.4%. Conclusion: The g1679C > G SNP in the NPC1L1 gene is critical and exerts a differential impact on the response to hyzetimibe treatment. Heterozygotic patients respond with poor efficacy when treated by monotherapy but show good responses in terms of LDL-C reduction when hyzetimibe was co-administered with atorvastatin. To treat hypercholesterolemia in a precise manner with hyzetimibe, it is necessary to identify genotype patients for the g1679C > G SNP. We also highlight the potential necessity for identifying the appropriate subjects to be treated with ezetimibe. Clinical Trial Registration: [https://clinicaltrials.gov/], identifier [CTR20150351]